Dependence of radiation belt flux depletions at geostationary orbit on different solar drivers during intense geomagnetic storms - Gokani, Sneha A.; Han, De-Sheng; Selvakumaran, R.; Pant, Tarun Kumar (Frontiers in Astronomy and Space Sciences, 2022)
The loss of outer radiation belt electron flux is widely studied in terms of the mechanism that brings in these losses. There are a few studies, which attempted to explain the interplanetary conditions that favor the depletions. As the Sun is the prime cause of any changes happening in the magnetosphere, it is important to look at the solar drivers that bring in such changes. In this paper we attempt to understand the effect of solar structures and substructures on the loss of radiation belt high energy electrons during intense geomagnetic storms. The superposed epoch analysis is used to observe any peculiar changes in GOES electron flux data during the storms that are associated with solar structures like CME and CIR, ICME substructures like magnetic cloud, magnetic cloud with sheath, ejecta, ejecta with sheath and only sheath. The long-term data also gave an opportunity to compare the flux decrease during solar cycle 23 and 24. It is observed that (a) CIR associated storms cause comparatively higher flux decrease than CME associated storms (b) sheath related storms bring out higher flux decrease, and (c) No significant change in flux for the storms of both the solar cycles. The flux decrease in intense storm at geostationary orbit is essentially triggered by the ‘Dst effect’. Apart from this, minimum IMF Bz, and northward IMF Bz before turning southward add on to the flux decrease. These results hold true for the electron depletions occurring only during intense geomagnetic storms and may alter otherwise.